Answer:
x=10
Step-by-step explanation:
first substitute y with the value (-5)
2x+5(-5)=-5 which is simplified to 2x+-25=-5
add 25 to -5 which gives you 2x=20
then divide 20 by 2 which makes x=10
Answer:
Therefore the required resulting equation is
![6x-15y=-63\\-15x+15y=90](https://tex.z-dn.net/?f=6x-15y%3D-63%5C%5C-15x%2B15y%3D90)
6 x minus 15 y = negative 63.
Negative 15 x + 15 y = 90
Step-by-step explanation:
Given:
......................Equation ( 1 )
......................Equation ( 2 )
To Find:
Expression after multiplying to eliminate y term,
Solution:
So to eliminate 'y' term we need to multiply equation 1 by a constant 3 and equation 2 by a constant -5, such that equations becomes
.....( 1 )
.....( 2 )
so now by adding new equation one and two we can eliminate y term that means -15y and +15y will get cancel,
Therefore the required resulting equation is
![6x-15y=-63\\-15x+15y=90](https://tex.z-dn.net/?f=6x-15y%3D-63%5C%5C-15x%2B15y%3D90)
6 x minus 15 y = negative 63.
Negative 15 x + 15 y = 90
Answer:
36π mi
Step-by-step explanation:
Area of a circle = πr²
Diameter = 12 mi. Therefore, radius=12/2 = 6 mi
πr²
π x (6)²
π x 36
Hence, the answer is 36π mi
Answer:
B. 95
Step-by-step explanation: